Concentrating omega-3 fatty acids in Nannochloropsis oceanica oil by using enzyme immobilized nano-silica systems. (20th June 2023) - Jain, Priyanshu; Mandal, Shovon; Minhas, Amritpreet Kaur; Puri, Munish; Barrow, Colin J.
Abstract: Burning agricultural waste causes local air pollution and global warming. Agricultural waste, such as rice husks, contains silica reserves that can be processed into nano silica and used as a substrate for the immobilization of enzymes. The present study attempts to develop efficient silica-based nano-biocatalysts for concentrating omega-3 fatty acids in algal oil by hydrolyzing specific short-chain fatty acids. In this regard, tetraethyl orthosilicate (TEOS) and rice husk ash (RHA) were used as precursors to obtain nano-silica supports. Candida rugosa lipase (CRL) was then physically adsorbed and chemically cross-linked onto the created silica nano supports. The immobilized nano-systems created using the physical adsorption approach showed the maximum binding efficiency and enzymatic activity of CRL. The protein content of the CRL physically adsorbed in TEOS was 925 mg/g, while the protein loading in the RHA systems was 938 mg/g. However, the enzymatic activity of the selected systems for hydrolyzing para nitro-phenol palmitate (100 mM PBS buffer at pH-7.2, for 10 min at 37 °C) was 56 units/mg for the RHA system and 707 units/mg for the TEOS system. These two nano-enzyme systems were utilized further to hydrolyze the Nannochloropsis oceanica oil, and a physically adsorbed CRL TEOS system was found to have a 2.5-fold enrichment in eicosapentaenoic acid (EPA) which is used in food and pharmaceutical applications. Graphical abstract: Image 1 Highlights: From rice husk and tetraethyl orthosilicate, nono silica is produced and characterized. Candida rugose lipase (CRL) was immobilized onto the silica nano supports. Physically adsorbed CRL showed higher enzymatic activity. Nanosilica-immobilized CRL concentrates omega-3 fatty acids in algal oil.